ISTRI IDEAL DALAM PERSPEKTIF HADIS (TELAAH SANAD DAN MATAN) - Durotun Nafisah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
The ideal wife in everyday life is the dream of every husband. The paradigm of an ideal wife actually has been declared bythe Prophet Mohammad in some tradition is very clear. Those hadith also has a strong base and attachment to the Koran. This paperdescribes about some hadiths that explain about the criteria for ideal wives. Is based on a review of hadith criticism, and criticism of isnaad. Inthis paper, we found four traditions whose theme is the ideal wife, including and ahad hadith and muttasil onsanad, that we described basedon a review of isnaad and matan